The ties to unbind: age-related differences in feature (un)binding in working memory for emotional faces - Pehlivanoglu, Didem; Jain, Shivangi; Ariel, Robert; Verhaeghen, Paul (Frontiers in Psychology, 2014)
In the present study, we investigated age-related differences in the processing of emotional stimuli. Specifically, we were interested in whether older adults would show deficits in unbinding emotional expression (i.e., either no emotion, happiness, anger, or disgust) from bound stimuli (i.e., photographs of faces expressing these emotions), as a hyperbinding account of age-related differences in working memory would predict. Younger and older adults completed different N-Back tasks (side-by-side 0-Back, 1-Back, 2-Back) under three conditions: match/mismatch judgments based on either the identity of the face (identity condition), the face’s emotional expression (expression condition), or both identity and expression of the face (binding condition). Both age groups performed more slowly and with lower accuracy in the expression condition than in the binding condition, indicating the presence of an unbinding process. This unbinding effect was more pronounced in older adults than in younger adults, but only in the 2-Back task. Thus, older adults seemed to have a specific deficit in unbinding in working memory, over and beyond age-related differences observed in perceptual processing (0-Back) and attention/short-term memory (1-Back). Additionally, no age-related differences were found in accuracy in the 0-Back task, but such differences emerged in the 1-Back task, and were further magnified in the 2-Back task, indicating independent age-related differences in attention/short-term memory and working memory. Pupil dilation data confirmed that the attention/short-term memory version of the task (1-Back) is more effortful in older adults than younger adults.